2020
DOI: 10.1051/shsconf/20207406003
|View full text |Cite
|
Sign up to set email alerts
|

The impact of economic policy instruments on the conditions of sustainable economic growth

Abstract: Given the low rates of economic growth in Russia and the aggravation of the geopolitical situation, the question of the prospects for its stimulation with fiscal and monetary policy tools is of particular relevance. The main priority of the economic policy is to ensure financial stability and prevent destabilization, taking into account the volatility of hydrocarbons prices and the geopolitical tensions. The article uses dialectical materialistic and concrete historical methods to protect that the current econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In Russia, at the time of the introduction of inflation targeting, the relative amount of bank debt of non-financial corporations and the population was 55% of GDP. This was slightly inferior to its average level at the time of the introduction of this regime by other countries-59.4% (Altunyan et al 2020). However, given that the main group of countries switched to inflation targeting of the 2008-2009 world financial crisis, and developed countries even earlier-in the 1990s, the lag has now grown (Kitrar 2021).…”
Section: Resultsmentioning
confidence: 86%
“…In Russia, at the time of the introduction of inflation targeting, the relative amount of bank debt of non-financial corporations and the population was 55% of GDP. This was slightly inferior to its average level at the time of the introduction of this regime by other countries-59.4% (Altunyan et al 2020). However, given that the main group of countries switched to inflation targeting of the 2008-2009 world financial crisis, and developed countries even earlier-in the 1990s, the lag has now grown (Kitrar 2021).…”
Section: Resultsmentioning
confidence: 86%
“…30 Net public wealth used to be positive and substantial in all Western countries in 1978; the government owned between 15 percent and 25 percent of national wealth in the United States, Japan, France, Germany, and Britain in the mid-1970s. This mixed economy regime resulted from a combination of low public debt (following post-World War II debt restructuring and inflation) and a large public sector, including in some cases government ownership of large companies in banking and 30 We present two alternative series on the public share in China's national wealth, depending on what fraction of agricultural land is assigned to the government and the private sector (see the discussion in Section IA). This makes a significant difference at the beginning of the period (given the importance of agricultural land in 1978), but has relatively little effect in 2015 (see online Appendix Figure A2).…”
Section: A the Evolution Of Wealth-income Ratios And Public Propertymentioning
confidence: 99%
“…In reality, this relationship is related to long-term financial development. (Altunyan et al, 2020) investigated the effect of economic policy instruments on the growth conditions of sustainable development in Russia. They suggested that in order to achieve sustainable development and create social sustainability, the problem of equitable distribution should be solved through the application of financial policies.…”
Section: Literature Reviewmentioning
confidence: 99%